2011
DOI: 10.1111/j.1469-0691.2010.03369.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of unknown ocular pathogens in clinically suspected eye infections using ribosomal RNA gene sequence analysis

Abstract: DNA sequence-based identification of pathogens from ocular samples of patients with clinically suspected eye infections was accomplished using 16S and internal transcribed spacer (ITS) ribosomal RNA gene sequence analysis. PCR was positive for 24 of 99 samples tested. Both culture and 16S rDNA sequence analysis identified Pseudomonas aeruginosa, streptococci and Enterobacteriaceae. Isolates misidentified as Burkholderia cepacia by biochemical tests were identified as Ralstonia mannitolilytica by 16S rDNA seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 15 publications
3
20
0
Order By: Relevance
“…Disseminated and severe infections were commonly associated with solid organ transplantation and other immunosuppressive conditions (3,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Considering that the morphological identification of black fungi, and of Phaeoacremonium in particular, is problematic (28) and relies on sequencing of the internal transcribed space (ITS) ribosomal DNA (rDNA) region or ␤-tubulin or calmodulin genes (29)(30)(31), many cases in routine microbiology laboratories may have passed unnoticed (28). Also, there is a paucity of data pertaining to the antifungal therapy of infections due to these molds as no specific therapeutic regimen has been defined (32).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Disseminated and severe infections were commonly associated with solid organ transplantation and other immunosuppressive conditions (3,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Considering that the morphological identification of black fungi, and of Phaeoacremonium in particular, is problematic (28) and relies on sequencing of the internal transcribed space (ITS) ribosomal DNA (rDNA) region or ␤-tubulin or calmodulin genes (29)(30)(31), many cases in routine microbiology laboratories may have passed unnoticed (28). Also, there is a paucity of data pertaining to the antifungal therapy of infections due to these molds as no specific therapeutic regimen has been defined (32).…”
mentioning
confidence: 99%
“…The organisms were identified to the species level by sequencing of the internal transcribed spacer regions of the rDNA region and partial ␤-tubulin gene (20,(29)(30)(31).…”
mentioning
confidence: 99%
“…In 2011 two Phaeoacremonium species were newly isolated from human infections. P. minimum was identified as the etiologic agent of a subcutaneous phaeohyphomycosis in Korea (Choi et al 2011) and Phaeoacremonium inflatipes was identified from an eye infection in the Philippines (Daroy et al 2011). Only one animal infection is known namely of P. parasiticum that was isolated from the blood and urine of a dog in California that had renal failure ).…”
Section: )mentioning
confidence: 98%
“…To et al (2012) reported for the first time a culture-proven P. parasiticum respiratory tract infection in a severely immunocompromised patient and a case of airway colonization by P. parasiticum in a patient with past history of pulmonary tuberculosis. Two cases of eye infections caused by P. rubrigenum (Mostert et al 2005) and P. parasiticum (Daroy et al 2011) most probably also originated from aerial spores. A hospital ice dispenser was recently identified as source of P. parasiticum, which was associated with deficiencies in equipment cleaning (Blake et al 2014).…”
Section: Humansmentioning
confidence: 99%
See 1 more Smart Citation